Inorganic and Metallic Nanotubular Materials Recent Technologies and Applications - Kijima, Tsuyoshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book describes the synthesis, characterization and applications of inorganic and metallic nanotubular materials. It cover a wide variety of nanotubular materials excluding carbon nanotubes, ranging from metal oxides, sulfides and nitrides such as titanium oxide, tungsten sulfide, and boron nitride, as well as platinum and other noble-metals to unique nanotubes consisting of water, graphene or fullerene. Based on their structural and compositional characteristics, these nanotubular materials are of importance for their potential applications in electronic devices, photocatalysts, dye-sensitized solar cells, nanothermometers, electrodes for fuel cells and batteries, sensors, and reinforcing fillers for plastics, among others. Such materials are also having a great impact on future developments, including renewable-energy sources as well as highly efficient energy-conversion and energy-saving technologies. This book will be of particular interest to experts in the fields of nanotechnology, material science and inorganic and solid-state chemistry, as well as graduate students in chemistry and physics.
to Inorganic and Metallic Nanotubes -- Synthesis and Applications of Titanium Oxide Nanotubes -- Synthesis, Structural Analysis, and Applications of Titanium Oxide Nanotubes -- Synthesis and Applications of Titanium Oxide Nanotube Thin Films -- Synthesis and Application of Titanium Oxide Nanohole Arrays -- Synthesis and Applications of Manganese Oxide Nanotubes -- Synthesis and Applications of Molybdenum Oxide Nanotubes -- Synthesis and Applications of Rare-Earth Compound Nanotubes -- Synthesis and Applications of Zirconia and Ruthenium Oxide Nanotubes -- Conversion of Metal Oxide Nanosheets into Nanotubes -- Synthesis and Applications of Mixed Oxide Nanotubes -- Synthesis and Applications of Imogolite Nanotubes -- Structure and Properties of Imogolite Nanotubes and Their Application to Polymer Nanocomposites -- Synthesis and Applications of Chalcogenide Nanotubes -- Synthesis and Functions of Fullerene Nanotubes -- Synthesis and Applications of Noble-Metal Nanotubes -- Synthesis and Applications of Magnetic-Metal Nanotubes -- Synthesis and Applications of Water Nanotubes -- Design and Synthesis of Titanium Oxide Nanotubes -- In Situ TEM Electrical and Mechanical Probing of Individual Multi-walled Boron Nitride Nanotubes.
Keywords: Engineering; Nanotechnology; Materials; Materials Science; Nanotechnology; Metallic Materials; Solid State Physics; Spectroscopy and Microscopy; Engineering, general